(untitled) - Moller, Heike

Characterisation and detection of mefenoxam sensitivity in phytophthora nicotianae and phytophthora citrophthora from citrus in South Africa (Stellenbosch : Stellenbosch University, 2024)
Thesis (MScAgric)--Stellenbosch University, 2024.